PENGGUNAAN PERISA BUAH UNTUK MEMPERBAIKI PROFIL SENSORIS MINUMAN SUSU KEDELAI HITAM FERMENTASI - , DINAR PATRIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Black soybeans have the potency to be developed to increase the diversification of food, one of them is a drink made from fermented black soy milk, remembering that beverages are very suitable in Indonesia because it gives a refreshing sensation. Soy-based products have sensory properties such as beany flavor, chalky, astringent, bitter, etc. In this study will be made a fermented black soy milk drink with the addition of fruits flavor and examined their effects on sensory properties. Drinks are formulated based on total solids, total sugar, and viscosity test and also the addition of flavor. Sensory properties of beverages tested include beany, chalky, creamy, sweet, nutty, viscous, and acid by trained panelists. Five drink formulas are made by dilution of fermented black soy milk: water = 1:1, the addition of 5% sugar, and the addition of mango, jackfruit, pineapple, melon, guava flavor 0.5% respectively. The results of sensory evaluation showed that the addition of flavor drinks can mask beany flavor and nutty, creamy sensation and enhance the viscous, sweet and sour sensation strengthen, and able to cover the sensation of chalky of black soybeans fermented milk drinks.